Formacion profesional: mito y realidad - Vargas Morales, Zenon (2005)
To the u niversity young people who in year 2002 have concluded their professional studies in the Greater National University of San Marcos, touched extremely difficult a national and university scene to them for its professional formation: they are the students who had entered the university beween the years of 1997 and 1998, when by a side the university was taken under the defense military, Alberto Fujimori, it appealed to all the averageones to obtain his re-election and soom it would come the election of Alejandro Toledo and the revelation about the corruption. It is this scene that the young students assimilate and share certain values, beliefs, attitudes, conduts, language; as well as its protests and fights by a democratic society and of state of law.